2022
DOI: 10.7150/ijbs.72014
|View full text |Cite
|
Sign up to set email alerts
|

HERC3 directly targets RPL23A for ubiquitination degradation and further regulates Colorectal Cancer proliferation and the cell cycle

Abstract: Aims : Colorectal cancer (CRC) has high mortality and morbidity rates; however, the mechanism of CRC cells uncontrolled proliferation is unclarified, E3 ligases are widely reported to have crucial functions in cancers. HERC3 was once recognized as an important role in CRC, however its effects on CRC cell proliferation and cell cycle are blank. Methods : Correlation between HERC3 and clinical characteristics was analyzed. Coimmunoprecipitation, mass spectrometry analysis and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Considering that HERC3 is primarily localized in the cytoplasm (Cruz et al, 2001), it is reasonable that HERC3 primarily acts on the misfolded CFTR dislocated to the cytoplasm. Moreover, this presumed function is in line with previous findings that HERC3 promotes the proteasomal degradation of cytosolic proteins such as RPL23A (Zhang et al, 2022b), EIF5A (Zhang et al, 2022a), and SMAD7 (Li et al, 2019). On the other hand, HERC3 appears to be at least partially involved in retrotranslocation, and its contribution may be particularly important when the function of RNF5/185 is insufficient.…”
Section: Discussionsupporting
confidence: 90%
“…Considering that HERC3 is primarily localized in the cytoplasm (Cruz et al, 2001), it is reasonable that HERC3 primarily acts on the misfolded CFTR dislocated to the cytoplasm. Moreover, this presumed function is in line with previous findings that HERC3 promotes the proteasomal degradation of cytosolic proteins such as RPL23A (Zhang et al, 2022b), EIF5A (Zhang et al, 2022a), and SMAD7 (Li et al, 2019). On the other hand, HERC3 appears to be at least partially involved in retrotranslocation, and its contribution may be particularly important when the function of RNF5/185 is insufficient.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the HECT domain in Herc3 is functional and able to bind ubiquitin (and undergo ubiquitination) 61 . Within the last 2 years, this HECT domain of Herc3 has also been shown to ubiquitinate RPL23A 65 , EIF5A2 66 , and ERK2 67 and target them for degradation. Herc3 may also have important biological functions that are independent of the RLD and HECT domains.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its suggested involvement in ubiquitination, HERC3 is an understudied member of the HERC family with limited functional implications, especially in cancer. HERC3 targets few substrates for ubiquitinationdependent degradation, including SMAD7, MM1, EIF5A2, and RPL23A (Chen et al, 2018;Li et al, 2019;Zhang et al, 2022aZhang et al, , 2022b. In addition, HERC3 can inhibit NF-jB signaling independent of its E3 activity (Hochrainer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…HERC3 could also facilitate ubiquitinationmediated degradation of SMAD7 to positively regulate TGF-b signaling in glioblastoma (Li et al, 2019). Recent studies found that HERC3 targets degradation of EIF5A2 and RPL23A to potentially block cell proliferation and metastasis in colorectal cancer (Zhang et al, 2022a(Zhang et al, , 2022b. In addition, HERC3 promotes RelA degradation independent of its E3 activity to inhibit NF-jB signaling (Hochrainer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%